2017
DOI: 10.3389/fevo.2017.00122
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Arch-Style Road Crossing Structures from Relative Movement Rates of Large Mammals

Abstract: In recent decades, an increasing number of highway construction and reconstruction projects have included mitigation measures aimed at reducing wildlife-vehicle collisions and maintaining habitat connectivity for wildlife. The most effective and robust measures include wildlife fences combined with wildlife underpasses and overpasses. The 39 wildlife crossing structures included along a 90 km stretch of US Highway 93 on the Flathead Indian Reservation in western Montana represent one of the most extensive of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…There are many different types of wildlife crossing structures, but of the designs available to them, pumas ( Puma concolor ) appeared to have a preference for open-span bridge underpasses over other types (Gloyne and Clevenger 2001). The location of wildlife crossing structures may, however, be more important than their design (Andis et al 2017). Crossing structures should be constructed where they would have maximum impact, such as at the hotspots identified, or in areas frequently crossed by cheetahs, or along roads that bisect areas with high cheetah utilization, density or occupancy (Smith et al 2015), following best practice guidelines (Trocmé 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many different types of wildlife crossing structures, but of the designs available to them, pumas ( Puma concolor ) appeared to have a preference for open-span bridge underpasses over other types (Gloyne and Clevenger 2001). The location of wildlife crossing structures may, however, be more important than their design (Andis et al 2017). Crossing structures should be constructed where they would have maximum impact, such as at the hotspots identified, or in areas frequently crossed by cheetahs, or along roads that bisect areas with high cheetah utilization, density or occupancy (Smith et al 2015), following best practice guidelines (Trocmé 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Crossing structures should be constructed where they would have maximum impact, such as at the hotspots identified, or in areas frequently crossed by cheetahs, or along roads that bisect areas with high cheetah utilization, density or occupancy (Smith et al 2015), following best practice guidelines (Trocmé 2015). Crossing structures are commonly used by large carnivores (Grilo et al 2008, Andis et al 2017) so it is reasonable to expect that Asiatic cheetahs will also use them, although confirming this would require monitoring. While wildlife crossing structures are successful at reducing road mortality, they do not keep animals off the road: to achieve this fencing is also required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Southern California, bobcats and coyotes tended to use passages in areas surrounded by less human development (Ng et al 2004). Andis et al (2017) compared large mammal movement between arch-style underpasses and the surrounding habitat. They found that mule deer used the underpasses significantly more, while black bear and coyote were detected as expected based on movement through the surrounding habitat.…”
Section: Temporal and Spatial Variationmentioning
confidence: 99%